Antropologi dan Persoalan Perubahan Iklim: Perspektif Kritis Ekologi Politik - Suraya Afiff (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2022)
Climate change could cause devastating impacts on Indonesia. The sea-level rise triggered by anthropogenic climate change, for example, will be affecting coastal infrastructure since Indonesia is ranked as the second country with the longest coastline in the world. Moreover, more than 100 million people (or about sixty percent of the total population in Indonesia) who live along Indonesia's coastline area would also be affected by sea-level rise. It is obviously clear the significance of social, cultural, political, and economic dimensions of climate change problems. Therefore, for anthropology, climate change should be one of the important research subjects that need our attention. And yet, anthropological study on climate change is still limited in Indonesia. My intention is to explore the theoretical approach that Indonesian anthropologists used to study climate change issues. Based on the number of existing studies, Indonesian scholars tend to use cultural ecology and cultural interpretation as the common theoretical approach in their study of the subject. Meanwhile, the critical anthropology perspective has been the least known perspective used by scholars in Indonesia. For this reason, my objective is to introduce political ecology as part of the critical anthropology approach as the theoretical option available in the study of climate change issues. Based on the literature study, I provide a brief introduction to the emergence of the political ecology approach in the study of human-environment interrelationship and how climate change problems were viewed from the political ecology perspective. The article also discusses possible research questions and issues that could be generated using the political ecology framework.